Long telomeres in peripheral blood leukocytes are associated with an increased risk of soft tissue sarcoma. Issue 10 (13th February 2013) - Xie, Hui; Wu, Xifeng; Wang, Shui; Chang, David; Pollock, Raphael E.; Lev, Dina; Gu, Jian
Abstract BACKGROUND: Human telomeres consisting of long, tandem repeats of the nucleotide sequence TTAGGG at the chromosome ends are essential for maintaining chromosomal stability. Previous epidemiologic studies have indicated that shorter telomere length in peripheral blood leukocytes (PBLs) is associated with the development of many cancers. However, the relation between PBL telomere length and the risk of soft tissue sarcoma (STS) has not been investigated. METHODS: The relative telomere length (RTL) was determined in PBLs using real‐time polymerase chain reaction in this case‐control study. The study participants included 137 patients with histologically confirmed STS (cases) who had received no prior chemotherapy or radiotherapy and 137 healthy controls who were frequency‐matched to cases on age, sex, and ethnicity. RESULTS: Patients in the case group had significantly longer RTL than controls (1.46 ± 0.42 for cases vs 1.15 ± 0.39 for controls; P < .001). By using median RTL in the controls as a cutoff level, individuals who had long telomere length were associated with a significantly increased risk of STS compared with those who had short telomere length (adjusted odds ratio, 4.71; 95% confidence interval, 2.63‐8.44). When participants were categorized further into 3 or 4 groups according to the tertile or quartile RTL values of healthy controls, a significant dose‐response relation was observed between longer RTL and increased risks of STS. CONCLUSIONS: The current results provided the first epidemiologic evidence that longer telomere length in PBLs is associated significantly with an increased risk of STS, potentially suggesting an important role for telomere maintenance in STS development. Cancer 2013. © 2013 American Cancer Society.